Noninvasive Brain Stimulations for Unilateral Spatial Neglect after Stroke: A Systematic Review and Meta-Analysis of Randomized and Nonrandomized Controlled Trials - Kashiwagi, Flavio Taira [UNESP]; El Dib, Regina [UNESP]; Gomaa, Huda; Gawish, Nermeen; Suzumura, Erica Aranha; Silva, Tais Regina da [UNESP]; Winckler, Fernanda Cristina [UNESP]; Souza, Juli Thomaz de [UNESP]; Conforto, Adriana Bastos; Luvizutto, Gustavo Jose; Bazan, Rodrigo [UNESP] (Hindawi Ltd, 2018)
Background. Unilateral spatial neglect (USN) is the most frequent perceptual disorder after stroke. Noninvasive brain stimulation (NIBS) is a tool that has been used in the rehabilitation process to modify cortical excitability and improve perception and functional capacity. Objective. To assess the impact of NIBS on USN after stroke. Methods. An extensive search was conducted up to July 2016. Studies were selected if they were controlled and noncontrolled trials examining transcranial direct current stimulation (tDCS), repetitive transcranial magnetic stimulation (rTMS), and theta burst stimulation (TBS) in USN after stroke, with outcomes measured by standardized USN and functional tests. Results. Twelve RCTs (273 participants) and 4 non-RCTs (94 participants) proved eligible. We observed a benefit in overall USN measured by the line bisection test with NIBS in comparison to sham (SMD -2.35, 95% CI -3.72, -0.98; p = 0 0001); the rTMS yielded results that were consistent with the overall meta-analysis (SMD -2.82, 95% CI -3.66, -1.98; p = 0 09). The rTMS compared with sham also suggested a benefit in overall USN measured by Motor-Free Visual Perception Test at both 1 Hz (SMD 1.46, 95% CI 0.73, 2.20; p < 0 0001) and 10 Hz (SMD 1.19, 95% CI 0.48, 1.89; p = 0 54). There was also a benefit in overall USN measured by Albert's test and the line crossing test with 1 Hz rTMS compared to sham (SMD 2.04, 95% CI 1.14, 2.95; p < 0 0001). Conclusions. The results suggest a benefit of NIBS on overall USN, and we conclude that rTMS is more efficacious compared to sham for USN after stroke.